2013
DOI: 10.1038/srep01904
|View full text |Cite
|
Sign up to set email alerts
|

Skin Stem Cell Hypotheses and Long Term Clone Survival – Explored Using Agent-based Modelling

Abstract: Epithelial renewal in skin is achieved by the constant turnover and differentiation of keratinocytes. Three popular hypotheses have been proposed to explain basal keratinocyte regeneration and epidermal homeostasis: 1) asymmetric division (stem-transit amplifying cell); 2) populational asymmetry (progenitor cell with stochastic fate); and 3) populational asymmetry with stem cells. In this study, we investigated lineage dynamics using these hypotheses with a 3D agent-based model of the epidermis. The model simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 59 publications
1
63
0
Order By: Relevance
“…The self-renewal capability observed in cells from the α6-integrin bri /CD71 dim subpopulation in HaCaT cells reported in this work, was similar to that reported in several works in the identification of both adult normal and cancer stem cells, where the isolated progenitor subpopulation was also able to reestablish the initial phenotype of the total population, increasing also the number of putative “progenitor” cells after each cycle of separation [46, 59, 60]. However, in a clear contrast with cancer stem cells, putative progenitor cell population in HaCaT was considerably lower and its enrichment after reseeding was not exponential.…”
Section: Discussionsupporting
confidence: 89%
“…The self-renewal capability observed in cells from the α6-integrin bri /CD71 dim subpopulation in HaCaT cells reported in this work, was similar to that reported in several works in the identification of both adult normal and cancer stem cells, where the isolated progenitor subpopulation was also able to reestablish the initial phenotype of the total population, increasing also the number of putative “progenitor” cells after each cycle of separation [46, 59, 60]. However, in a clear contrast with cancer stem cells, putative progenitor cell population in HaCaT was considerably lower and its enrichment after reseeding was not exponential.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, phenotypic variability may be triggered by noise because fluctuations enable the exploration of the phase space through different types of dynamics891011. This variability has been observed in several natural systems such as the galactose utilization network in budding yeast12, the process of DNA uptake from the environment in B. subtilis1314, photoreceptor differentiation in the fruit fly retina15 and stem cell differentiation161718. By combining mathematical modeling and gene expression studies in zebrafish, Zhang et al demonstrated that noisy expression can actually facilitate boundary sharpening19.…”
mentioning
confidence: 99%
“…They looked at transport and nutrient intake, cell population, ECM deposition, cell attachment, and migration . Agent‐based models have been used to investigate the role of growth factors, organisation of keratinocytes, presence of fibroblasts, and the importance of stem cells in long‐term skin epithelium regeneration . In silico models may be useful theoretically and in combination with other models but are lacking the physical characteristics of human skin …”
Section: Resultsmentioning
confidence: 99%